Reaction on the comments on the ENCJ study on Method for Assessment of Judicial Independence and Accountability. - Frans van Dijk; Philip Langbroek (International Journal for Court Administration, 2018)
We are grateful for the contribution of Stefan Voigt, Elaine Mak, David Kosař, Samuel Spáč, Ingo Keilitz and Marco Fabri to this Special Issue.  Their commentaries on the indicators for independence and accountability of the judiciary as developed for the ENCJ give many useful ideas for future development. The comments also reflect the different disciplinary backgrounds of the authors and point to the need to position the ENCJ approach within the diverse disciplines that engage in the analysis of judicial independence. It is obvious that the approaches of the commenters on the ENCJ study differ widely. In economics the approach focuses on measuring independence for inclusion as variable in econometric models about, for instance, economic growth or protection of property rights. More (de-facto) independence enhances economic performance, but how more independence is to be achieved is not addressed.  From the perspective of performance management of organizations, independence is part of court performance for the clients and to some degree subservient to it. In a legal, descriptive approach, the situation in different countries is described in detail, also as a part of judicial culture. The ENCJ study only sets criteria for measuring judicial independence, and does not address performance measurement of courts and judges in general.